Frequency selective digital predistortion for harmonic rejection. Issue 10 (3rd October 2018) - Wu, Xiaofang; Cai, Xinshuo; Huang, Jinfu; Shi, Jianghong
ABSTRACT: In recent wireless communications, spectrally flexible transmissions such as carrier aggregation and cognitive radio pose severe challenges for the high-efficient radio-frequency power amplifier (PA) design. The non-linear characteristics of PAs may yield substantial unwanted emissions that can violate the emission limits, thus interfere with other communication systems within the frequency vicinity. Furthermore, in frequency-division duplexing systems, if the unwanted emissions happen to fall into the intended receiver band, it may cause severe receiver desensitisation. In this paper, we present a novel digital predistortion (DPD) technique based on a frequency selective architecture, which is aimed at reducing the unwanted harmonic emissions at any pre-specified frequency and linearising the fundamental signal at the same time. The method can simplify the predistortion structure compared with the whole spurious suppression DPD method and thus reduce the computational complexity of the predistortion process. Furthermore, the identification of the DPD coefficients is based on a breeding particle swarm optimisation algorithm, which can enhance the calculation flexibility as well accelerate the convergence speed compared with traditional gradient methods. Both simulation and measurement results demonstrate sufficient spur suppression at the target frequency.